Assessment of caffeine content in some energy drink sold in ekwulobia - Nebechi Ezeofor; Ezeofor (Institute of Computer Science (IOCS), 2022)
Caffeine is a naturally occurring chemical stimulant found in leaves, seeds and fruits of numerous plant species of groups of nitrogenous organic compound of the alkaloid group called trimethylxanthine. Energy drinks are non-alcoholic beverage that contain high level of substances capable of exciting any bodily functions and tends to stimulate the brain and the central nervous system. The aim and objective of the research is to determine the caffeine content and concentration of caffeine of five (5) different beverages (energy drink) sold in Ekwulobia in Aguata local Government Area. The caffeine content in the drink by name predator, fearless, bullet, climax and power horse were determined. The result showed the level of caffeine in the respective energy drink brand as 0.721mg/L for predator (PRE 101), 0.545mg/L for fearless ( FEA 102), 0.275 mg/L for bullet (BUL 103), 0.305 mg/L for climax (CLI 104) and 1.135 mg/L power horse (POW 105). The result showed that the caffeine content in the energy drink samples were significantly lower than the authorized level of (32mg/100L) recommended by World Health Organization which means that the energy drink analyzed are safe for consumption. .